Hubungan Tingkat Stres dengan Kejadian Sleep paralysis pada Mahasiswa Sarjana Keperawatan Tingkat Akhir - Andria Pragholapati; Rizki Muliani; Intan Permatasari Lestari (Jurnal Kesehatan dr. Soebandi, 2020)
Sleep paralysis is an inability to move muscles during the transition between asleep and awakening with or without halusinations and occurred relatively in a short time. Sleep paralysis causes by lack of sleep, sleeping on the back, narcolepcy, chemical abused and stress. Sleep paralysis is most common in college students (28%) because they got more stressor. This research was suposed to examined the relationship between stress and the occurrence of sleep paralysis This research the descriptive correlation method with cross sectional approach. 65 college students were participated as the sample from the whole 71 population of college students that taken by accidental sampling tecnique. These research used the descriptive correlation method with cross sectional approach. The instrument of this study was the SSI (Student-Life Stress Inventory) questionnaire to measure the stress level, whereas the occurrence of sleep paralysis measured by the questionnaire which adopted from the USEQ (The Unusual Sleep Experience). Statistic Chi-square test was done to analyzed that both variables with (ɑ) = 0.01. 40 college students (61.5%) with mild level of stress was identified that 21 college students (52.5%) were experienced the occurrence of sleep paralysis, and 14 college students (47.5%) were not experienced the occurrence of sleep paralysis. wheareas 25 college students (38,5%) with low level of stress, were not experienced the occurrence of sleep paralysis. The result showed that there was a relationship between stress and the occurrence of sleep paralysis with p value (0.000) < 0.01. Suggestion for the institute is to give a regular counseling program or facilitated college students so they got some positive activities such as organization enlarge or some interesting,variative and innovative UKM that could be the stress release.